Functional characteristics of a double negative feedback loop mediated by microRNAs - Cai, Shuiming (Springer Netherlands, 2013)
MicroRNAs (miRNAs) are a class of small, noncoding RNAs that play crucial roles in almost all cellular processes. As key post-transcriptional regulators of gene expression, miRNAs mainly induce mRNA degradation or translational repression. Recently computational and experimental studies have identified an abundance of motifs involving miRNAs and transcriptional factors (TFs). Here, we study the functional characteristics of one such motif, a two-node miRNA-mediated double negative feedback loop (MDNFL) in which a TF suppresses an miRNA and the TF itself is negatively regulated by the miRNA. Several examples of this motif are described from the literature. We propose a general computational model for the MDNFL based on biochemical regulations and explore its dynamics by using bifurcation analysis. Our results show that the MDNFL can behave as a bistable switch. This functional feature is in agreement with experimental observations of the widespread appearance of miRNAs in fate decisions such as differentiation during development. Importantly, it is found that under the interplay of a TF and an miRNA, the MDNFL model can behave as switches for wide ranges of parameters even without cooperative binding of the TF. In addition, we also investigate how extrinsic noise affects dynamic behavior of the MDNFL. Interestingly, it is found that when the MDNFL is in the bistable region, by choosing the appropriate extrinsic noise source, the MDNFL system can switch from one steady state to the other and meanwhile the production of either miRNA or protein is amplified significantly. From an engineering perspective, this noise-based switch and amplifier for gene expression is very easy to control. It is hoped that the results presented here would provide a new insight on how gene expression is regulated by miRNAs and further guidance for experiments.